ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EMOSI POSITIF DAN DAMPAKNYA TERHADAP PEMBELIAN IMPULSIF PADA AIR ASIA INDONESIA - Murti, Aristya; Idris, Idris (Faculty of Economics and Business Diponegoro University, 2018)
This research is motivated by low consumer interest (positive emotion) in the prices offered by Air Asia Indonesia, even though the prices offered by Air Asia Indonesia are lower compared to other airlines This study aims to show the effect of hedonic consumption and sales promotion on impulsive buying through positive emotions on Air Asia Indonesia Departure of Soekarnoo-Hatta Airport.The population in this study are users of Air Asia Indonesia are taken by using is a non-probability sampling where the samples used were 150 respondents. Data obtained from the questionnaire which are processed and analyzed using Structural Equation Modeling through AMOS program.The results of the study found that the sales promotion and consumption hedonis have positive and significant effect on positive emotions, then positive emotions have a positive effect on impulsive buying. In addition, the two independent variables also have a positive and significant influence on Impulsive buying.